A NOTE ON GENSYS’ MINIMALITY - SACCAL, Alessandro (Theoretical and Practical Research in Economic Fields, 2021)
Gensys’ non-minimality is shown analytically and necessary and sufficient conditions for vector autoregression representations of states in outputs are presented.